Problematika Penumpukan Realisasi Anggaran di Akhir Tahun : (Studi Kasus di IAIN Sultan Amai Gorontalo) - Sri Dewi Yusuf; Siti Muthi’ah (Al-Buhuts, 2023)
This study aims to identify problems with the accumulation of budget realization at the end of the year at IAIN Sultan Amai Gorontalo. The method used is a qualitative method. The analytical tool used in this research is thematic analysis. The method chosen to recruit informants was expert analysis. Data collection procedures in qualitative research include interviews and documentation. The results showed that there were three main points of discussion that led to a buildup in the realization of the expenditure budget at the end of the year at IAIN Sultan Amai Gorontalo, namely budget planning, budget execution, and the quality of human resources. Good planning includes the preparation of detailed activities and budgets, the absence of blocked budgets and the absence of additional budgets determines the timely withdrawal of funds. While good implementation will depend on good planning too, if a budget plan is well structured and of good quality, then the implementation will also run effectively and efficiently. Likewise with the quality of competent human resources is one of the factors in achieving an organizational goal.